A luminescent probe containing a tuftsin targeting vector coupled to a terbium complex. - Aarons, R; Notta, J; Meloni, M; Feng, J; Vidyasagar, R; Narvainen, J; Allan, S; Spencer, N; Kauppinen, R; Snaith, J; Faulkner, S (2006)
Orthogonal protection strategies have been used to prepare a series of luminescent and MRI active lanthanide complexes containing a tuftsin targeting vector that are internalised by macrophage cells.